Podcast
Questions and Answers
What change would correct the error in the equation 2(x−4y)+3y=2x+11y?
What change would correct the error in the equation 2(x−4y)+3y=2x+11y?
- Change (x−4y) to (x+4y)
- Change 2(x−4y)+3y to 2(x+4y)−3y
- Change 2(x−4y)+3y to 2(x−4y)−3y (correct)
- Change 2x+11y to 2x−11y
Which correction is needed in the equation 2(x−4y)+3y=2x+11y?
Which correction is needed in the equation 2(x−4y)+3y=2x+11y?
- Change 2 times open paren x minus 4 y close paren plus 3 y to
- Change 2(x−4y)+3y to 2(x+4y)−3y
- Change open paren x minus 4 y close paren to (correct)
- Change 2x+11y to 2x−11y
What amendment would fix the mistake in the equation 2(x−4y)+3y=2x+11y?
What amendment would fix the mistake in the equation 2(x−4y)+3y=2x+11y?
- Change open paren x minus 4 y close paren to
- Change 2x+11y to 2x−11y
- Change 2 times open paren x minus 4 y close paren plus 3 y to
- Change (x−4y) to (x+4y) (correct)
Which modification is necessary for the equation 2(x−4y)+3y=2x+11y to be correct?
Which modification is necessary for the equation 2(x−4y)+3y=2x+11y to be correct?
What change would correct the error in the equation 2(x−4y)+3y=2x+11y?
What change would correct the error in the equation 2(x−4y)+3y=2x+11y?
Which modification is necessary for the equation 2(x−4y)+3y=2x+11y to be correct?
Which modification is necessary for the equation 2(x−4y)+3y=2x+11y to be correct?
What amendment would fix the mistake in the equation 2(x−4y)+3y=2x+11y?
What amendment would fix the mistake in the equation 2(x−4y)+3y=2x+11y?
Which correction is needed in the equation 2(x−4y)+3y=2x+11y?
Which correction is needed in the equation 2(x−4y)+3y=2x+11y?
Which correction would fix the error in the equation 2(x−4y)+3y=2x+11y?
Which correction would fix the error in the equation 2(x−4y)+3y=2x+11y?
What modification is necessary for the equation 2(x−4y)+3y=2x+11y to be correct?
What modification is necessary for the equation 2(x−4y)+3y=2x+11y to be correct?
What change would correct the error in the equation 2(x−4y)+3y=2x+11y?
What change would correct the error in the equation 2(x−4y)+3y=2x+11y?
Which amendment would fix the mistake in the equation 2(x−4y)+3y=2x+11y?
Which amendment would fix the mistake in the equation 2(x−4y)+3y=2x+11y?